Study of the wind energy development and the wind curtailment problem in China - Liu, Qian (My University, 2017)
The progressive trend in favor of renewable energy has been accelerating during the past few decades. This inclination for clean energy swept over the whole world and, China which is the biggest developing country and biggest energy consumer is also prominent in this trend. The installed capacity of renewable energy in China is growing faster than anywhere else. The Chinese government has been trying to facilitate the development of renewable energy including wind power, to act as alternatives to traditional energy sources. However, in the course of this development there are conflicts between power generation and power transmission, and conflicts between central government’s resolution for better environment and local government’s desire for GDP growth. The application of wind power encounters problems and difficulties through the years. This thesis endeavors to first present the real development condition of wind energy in China, to understand how it developed in this way, and then to analyze the influence of government policy, electricity price, and fuel price on wind-power electricity generators. The writer tries to shed some light on the remedy for current deficits
Master in the Electric Power Industry
Keywords: 33 Ciencias tecnológicas; 3322 Tecnología energética; 332205 Fuentes no convencionales de energía; 53 Ciencias económicas; 5312 Economía sectorial; 531205 Energía